Critical Care for the Patient With Multiple Trauma. (June 2016) - Radomski, Michal; Zettervall, Sara; Schroeder, Mary Elizabeth; Messing, Jonathan; Dunne, James; Sarani, Babak
Trauma remains the leading cause of death worldwide and the leading cause of death in those less than 44 years old in the United States. Admission to a verified trauma center has been shown to decrease mortality following a major injury. This decrease in mortality has been a direct result of improvements in the initial evaluation and resuscitation from injury as well as continued advances in critical care. As such, it is vital that intensive care practitioners be familiar with various types of injuries and their associated treatment strategies as well as their potential complications in order to minimize the morbidity and mortality frequently seen in this patient population.